Prevalence and genotype distribution of human papilloma virus in cervical samples of young married women: a hospital based prospective cross-sectional study - Bagde, Madhuri N.; Bagde, Nilajkumar D.; Deshmukh, Pooja; Negi, Sanjay; Thangaraju, Pugazhentan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of the study was to determine the prevalence and genotypes of human papillomavirus (HPV) infection in the cervical samples of young married women at a tertiary care hospital in Chhattisgarh. A prospective cross-sectional observational study was performed in married women, aged 18 to 30 years. Methods: Relevant history was noted and cervical samples were collected and tested for HPV deoxyribonucleic acid (DNA) by polymerase chain reaction (PCR). Data was compiled to calculate the prevalence of HPV and the genotypic distribution. Results: The overall prevalence of HPV in this study was 22.73% and that of type 16 and 18 either alone or in combination with other subtypes was 17.26%. They were the commonest subtypes. HPV positivity was inversely related to education levels (Chi square, p=0.05). There was a significant difference in parity of women testing positive for HPV versus those negative for HPV (one tailed Pr (t<t)=0.03, 95% CI=1.445 to 1,865 at 108 degrees of freedom). No difference was observed between education and socio economic levels of positive versus negative women. Type 16 and 18 accounted for 76% of all HPV subtypes detected. Conclusions: The prevalence of HPV infection is high in Indian women. The high risk oncogenic types are the commonest subtypes. There is an urgent need to screen for the presence of high risk HPV infections in younger women so that they may be followed up more closely to prevent cervical cancers.